2002
DOI: 10.1021/ja026713u
|View full text |Cite
|
Sign up to set email alerts
|

NMR Imaging of the Distribution of the Liquid Phase in a Catalyst Pellet during α-Methylstyrene Evaporation Accompanied by Its Vapor-Phase Hydrogenation

Abstract: This communication reports the first application of NMR imaging to study the progress of a multiphase heterogeneous catalytic reaction in situ. Various stationary regimes of alpha-methylstyrene (AMS) hydrogenation on a single Pt/gamma-Al2O3 catalyst pellet have been investigated. The two-dimensional maps of the liquid-phase distribution within the pellet have been obtained in the course of the catalytic reaction, with the pellet temperature rising up to 185 degrees C. The large liquid-phase concentration gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…We have employed a combination of NMR imaging (figure 9) and spectroscopy to visualize the processes in an operating single catalyst pellet [13,26,27] or in a granular catalyst bed. During the experiments, the catalyst (Pt/c-Al 2 O 3 ) is residing inside the rf coil of the NMR instrument, and the H 2 gas and the liquid reactant (a-methylstyrene, AMS) preheated to 68-80°C are supplied to the reaction volume.…”
Section: Coupling Of Mass Transport and Chemical Reactionmentioning
confidence: 99%
“…We have employed a combination of NMR imaging (figure 9) and spectroscopy to visualize the processes in an operating single catalyst pellet [13,26,27] or in a granular catalyst bed. During the experiments, the catalyst (Pt/c-Al 2 O 3 ) is residing inside the rf coil of the NMR instrument, and the H 2 gas and the liquid reactant (a-methylstyrene, AMS) preheated to 68-80°C are supplied to the reaction volume.…”
Section: Coupling Of Mass Transport and Chemical Reactionmentioning
confidence: 99%
“…Then, by definition, ϕ can be expressed as (10) The change in the thickness h dry of the dry surface layer according to expression (10) and Fig. 4a is equal to (11) The volume of the dry surface layer within which there is vapor-phase AMS hydrogenation is found as (12) β gas ShD AH /d eq = , D AH 6 10 5 -T gas /373 ( ) 1.9 , × = α gas Nuλ gas /d eq = , λ gas 0.216 T gas /373…”
Section: Estimation Of Parameters Of Mathematical Modelmentioning
confidence: 99%
“…For this purpose, the most promising experimental method is in situ NMR tomography (magnetic resonance microimaging) [7][8][9]. This method allows one, in particular, to obtain images of the liquid-phase distribution within the porous object and monitor the liquid-phase redistribution immediately during the process without destroying the object and without introducing any probes or molecular labels [10][11][12][13]. EXPERIMENTAL As a model reaction, we chose α -methylstyrene (AMS) hydrogenation to form cumene: C 6 H 5 C(CH 3 )=CH 2 + H 2 C 6 H 5 C(H)(CH 3 ) 2 .…”
mentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) imaging [9] offers certain advantages over other tomographic techniques. Recently it has been shown that NMR imaging can be successfully applied to map the liquid phase distribution within a functioning multiphase reactor [10,11] and to monitor the spatial variation of conversion along the length of the catalyst bed [12]. Under non-reactive conditions, the liquid holdup and the extent of surface wetting efficiency during trickle flow have been estimated with the use of two-dimensional (2D) and three-dimensional (3D) NMR imaging [13,14].…”
Section: Introductionmentioning
confidence: 99%